Harnessing imaging tools to guide immunotherapy trials: summary from the National Cancer Institute Cancer Imaging Steering Committee workshop. Issue 3 (March 2023) - Shankar, Lalitha K; Schöder, Heiko; Sharon, Elad; Wolchok, Jedd; Knopp, Michael V; Wahl, Richard L; Ellingson, Benjamin M; Hall, Nathan C; Yaffe, Martin J; Towbin, Alexander J; Farwell, Michael D; Pryma, Daniel; et al.
Summary: As the immuno-oncology field continues the rapid growth witnessed over the past decade, optimising patient outcomes requires an evolution in the current response-assessment guidelines for phase 2 and 3 immunotherapy clinical trials and clinical care. Additionally, investigational tools—including image analysis of standard-of-care scans (such as CT, magnetic resonance, and PET) with analytics, such as radiomics, functional magnetic resonance agents, and novel molecular-imaging PET agents—offer promising advancements for assessment of immunotherapy. To document current challenges and opportunities and identify next steps in immunotherapy diagnostic imaging, the National Cancer Institute Clinical Imaging Steering Committee convened a meeting with diverse representation among imaging experts and oncologists to generate a comprehensive review of the state of the field.